2019
DOI: 10.1371/journal.pone.0218608
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the awareness of stroke symptoms and emergency response by occupation in the Korean general population

Abstract: We evaluated the difference in awareness of stroke warning signs (SWS) and emergency response among occupational groups in the community-dwelling population. From the 2016 Korea Community Health Survey, a total of 10,445 individuals without stroke were included in the analysis. Multiple logistic regression analysis was used to explore the association of occupation with awareness of SWS and correct emergency response. SWS included the following: sudden numbness or weakness, sudden difficulty speaking or underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…16 Lack of knowledge of warning signs of stroke and inadequate emergency response often lead to delays in delivery medical/emergency care within the golden hour. 17 However, knowledge of immediate action that is necessary in dealing with a stroke patient can reduce both mortality and morbidity among stroke patients by preventing delay in hospitalization. 18 Low stroke awareness limits acute stroke care in high-risk populations and makes effective early treatment difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Lack of knowledge of warning signs of stroke and inadequate emergency response often lead to delays in delivery medical/emergency care within the golden hour. 17 However, knowledge of immediate action that is necessary in dealing with a stroke patient can reduce both mortality and morbidity among stroke patients by preventing delay in hospitalization. 18 Low stroke awareness limits acute stroke care in high-risk populations and makes effective early treatment difficult.…”
Section: Introductionmentioning
confidence: 99%
“… 16 Lack of knowledge of warning signs of stroke and inadequate emergency response often lead to delays in delivery medical/emergency care within the golden hour. 17 …”
Section: Introductionmentioning
confidence: 99%
“…However, further investigations are needed since some studies have also demonstrated contradictory results in that the urban residents knew more about the CVD symptoms ( 13 , 15 , 25 ). Socioeconomic factors such as high household income, high level of education, and white-collar occupations are known predictors of high knowledge of warning symptoms ( 13 17 , 19 , 20 , 25 ). This was also seen in our study, both for stroke and MI.…”
Section: Discussionmentioning
confidence: 99%
“…The stroke knowledge predictors held hugely debated in the literature. The education level is one of the most discussed factors [ 18 , 30 , 31 ]. As reported in the national data, our participants were mostly graduated from secondary school or university (61.6%).…”
Section: Discussionmentioning
confidence: 99%